2003
DOI: 10.1210/jc.2003-031008
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Replacement Therapy Is Associated with Less Coronary Atherosclerosis in Postmenopausal Women

Abstract: Most observational studies indicate that hormone replacement therapy (HRT) protects women from cardiovascular disease. Two recent randomized trials, however, showed no reduction in coronary events with HRT in postmenopausal women. A randomized study evaluating subclinical atherosclerosis showed a beneficial effect of estrogen. In the current study we evaluated the association between HRT and coronary artery atherosclerosis, as quantified by coronary artery calcium score. Current users of HRT were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…Some clinical studies now confirm higher calcium content in coronary plaques of women using hormone replacement therapy (HRT), 104,105 whereas other observational studies report reduction in coronary calcification with HRT. 106 Conclusions about the relationship between estrogen and coronary calcification cannot be reliably determined from observational studies. Unfortunately, the only data available now regarding estrogen and CAC are observational.…”
Section: Menopausementioning
confidence: 99%
“…Some clinical studies now confirm higher calcium content in coronary plaques of women using hormone replacement therapy (HRT), 104,105 whereas other observational studies report reduction in coronary calcification with HRT. 106 Conclusions about the relationship between estrogen and coronary calcification cannot be reliably determined from observational studies. Unfortunately, the only data available now regarding estrogen and CAC are observational.…”
Section: Menopausementioning
confidence: 99%
“…23 Apoptosis may also prevent atherosclerosis by reducing the cellular content and neointimal thickening of the plaque. However, increased apoptosis may render the plaques more vulnerable, especially at the shoulder region where the fibrous cap is thin.…”
Section: Cederholm Et Al Annexin V In Cardiovascular Disease 201mentioning
confidence: 99%
“…Conversely, studies in animals have shown that HRT can beneficially affect coronary artery atherosclerosis [38][39][40]. A recent large study of postmenopausal women has shown that HRT use is associated with less coronary atherosclerosis as measured by EBT [41]. This latter result suggests that a potential explanation for the conflicting animal and human data with HRT could be related to the proinflammatory and prothrombotic effect of such therapy on established vessel wall lesions, even with a potentially beneficial effect in suppressing lesion formation.…”
Section: Discussionmentioning
confidence: 99%